(untitled) (Research, Society and Development, 2020)
Aiming to study the behavior of Melon Caipira grown in trays with commercial substrate in the open and 50% shading, an experiment was carried out in a randomized block design with 4 replications and the treatments configured in a 2x4x2 factorial, (tray type: 72 and 128 cells; growth stage: one to four true leaves; environment: open sky and protected cultivation). The results showed that root height and length vary, regardless of the type of tray and environment, where indoor seedlings and 72-cell trays are larger. Such behavior is repeated in the measurement of growth stage and environment, where the seedlings obtained in trays of 72 cells showed bigger fresh mass of the aerial part. However, trays with 72 cells and a protected environment increase the relation between aerial part/root. It is concluded, therefore, that trays with 72 cells and the protected environment show more the growth of the aerial part, increasing the relationship between these segments. This way it is possible to perform the transplant until the fourth leaf stage using 72 cell trays; on the fourth leaf in open sky trays of 128 cells, and on the third, in protected cultivation.